Tratamientos periodísticos del femicidio en la Televisión Ecuatoriana. - Quillupangui Yasaca, Liliana Elizabeth (2018)
The purpose of this research is to investigate what is the management for audiovisual media gives the femicide news in Ecuador. The femicide is the death of a woman by the fact of being a woman which is provoked by her partner or a man or woman stranger. The objectives of this research are framed in knowing how the media broadcast the femicides news in specified in the program "Crónica viva" and "El mañanero" that are transmitted by TC televisión, in addition to categorize as the community understand this type of news. In Ecuador, there is a large number of this type of murders pontoon (2009) points out that, the current husband or partner was named as responsible for the violence in about 80% of cases. In life, 14% of women reported verbal violence, 17% verbal and physical, and the 9% verbal, physical and sexual abuse. In total, 46% of women who had been married or suffered at least one of the three types of violence. Due to the data obtained as a researcher examines what was the management that this type of programs gave some cases, it was taken as an example Sharon´s case in the year 2015 for being one of the first considered as a femicide, which also permitted to study more similar cases. After the application of specialized focus groups and interviews, it was determined that the media studied, do not have an adequate management of the information on femicide, it is determined that in some cases there is a double victimization by the poor management without a rights-based approach and gender.